INVESTIGATING THE POSSIBILITY OF ALLOYING AN ALLOY ALSI25CU5CR WITH CO, CR AND MO USING METAL POWDER (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
A base aluminium-silicon alloy AlSi25Cu5Cr was used to investigate the possibility of alloying aluminium alloys with hard-to-melt elements. The alloying elements Co, Cr and Mo were introduced into the melt using metal powder from a hard-melting dental cobalt-chromium-molybdenum alloy. The metal powder was packed in aluminium foil and introduced into the melt of the studied alloy at a temperature of 810º C. After alloying and mechanical stirring of the melt, it stood for 30 min. at a temperature, raised to 850º C and experimental castings were cast from it. After spectral analysis, the degree of absorption of the alloying elements by the aluminium melt was determined. The structure and mechanical properties of the thus obtained alloy were investigated.